PMT Based Targeting in Burkina Faso - Gunnemann, Julius (World Bank, Washington, DC, 2020)
Beneficiaries of the ongoing safety net program Burkin-Naong-Saya in Burkina Faso are selected based on a multi-step targeting strategy. One part of this strategy is Proxy Means Testing (PMT). The current PMT method, however, was developed using outdated 2009 data. This study uses a new, nationally representative household survey conducted in 2014 to evaluate the efficiency of updated PMT models. The findings are three-fold. First, a single national PMT model is preferable to urban/rural-specific models. Second, while the updated national model performs better than the old model in selecting the poorest urban households, it does not perform as well as the 2009 model in rural areas. Since rural areas are the current focus of the intervention, the PMT formula should not be changed. Third, parsimonious PMT models using only variables from HEA questionnaires are almost as efficient as models that use a much larger number of variables. This allows for PMT targeting based on HEA data, without the need for prior PMT data collection.